Digital method and algorithm for determining the coordinates of the «conditional» geometric center of an extended object from its binary radar image - Щербина, К.А.; Мсаллам, Е.П.; Вонсович, М.А.; Нежальская, К.Н.; Инкарбаева, О.С. (Radiotekhnika, 2020)
The features of the functioning of coastal radar information support, monitoring and control of the movement of marine vessels in the cramped conditions of navigation are examined and analyzed. The general issues and features of the optimization of digital processing of coordinate information in the near-radar sensing of extended marine objects under the influence of passive interference caused by the presence of the underlying sea surface and hydrometeorological formation in the form of rainfall are formulated and analyzed. Simple and effective digital algorithms have been developed for determining the azimuthal range-finding coordinates of extended objects from selected single and dispersed binary signal groups belonging to an extended radar object. The coordinates of the conditional geometric center, determined in accordance with the developed method, do not contain errors associated with the presence of a jib-trace. The results obtained by estimating the amount of mixing of the object when it moves along the channel are within the range of the real-expected values ΔD ≈ 15 meters. The developed method and its practical implementation are quite simple and effective in providing information support to the skipper in the process of escorting the vessel along the channel. Results fulfilled research in future will use in solving problem of determining the coordinates of the location of extended maritime object, as well as in the solution of similar problems when designing digital radar technics.